The sky above us - Sundin, Sarah (Sunrise at Normandy, 2019)
Numbed by grief and harboring shameful secrets, Lt. Adler Paxton ships to England with the US 357th Fighter Group in 1943. Determined to become an ace pilot, Adler battles the German Luftwaffe in treacherous dogfights in the skies over France as the Allies struggle for control of the air before the D-day invasion. Violet Lindstrom wanted to be a missionary, but for now she serves in the American Red Cross, where she arranges entertainment for the men of the 357th in the Aeroclub on base and sets up programs for local children. Drawn to the mysterious Adler, she enlists his help with her work and urges him to reconnect with his family after a long estrangement. Despite himself, Adler finds his defenses crumbling when it comes to Violet. But D-day draws near. And secrets can't stay buried forever.